Histological development of human foetal shoulder joint - Nazir, Sabia; Raina, Sunanda; Bashir, Zahid; Bano, Shamima; Shadad, Shaheen; Khan, Javed A.; Jan, Yasmeen (International Journal of Research in Medical Sciences, 2017)
Background: Shoulder joint is a multiaxial, diarthrodial joint of ball and socket variety. The various components of shoulder joint i.e. capsule, various ligaments, joint cavity and synovial tissue start developing in early embryonic and foetal life roughly in between 6th to 12th week of foetal development. The present study aims to analyze the sequences of development of various structures of shoulder joint in human embryo and compare the findings with other observers to gain some insight regarding its development and an attempt is made to correlate these observations clinically to analyze cause and management of recurrent shoulder dislocations. Methods: Shoulder joints of 32 foetuses collected from areas in and around Jammu were dissected properly and decalcified in Gooding and Stewart’s solution. Sections were cut after obtaining blocks by paraffin wax embedding method. Slides were stained using Haematoxylin and Eosin, Masson’s trichrome and orcein staining and important findings were documented. Results: The bony structures - head of humerus and glenoid fossa and joint cavity appear by 10 weeks which prolongs into bicipital sulcus by 12-1/2 weeks. Synovial tissue appears by 10 weeks and synovial villi appear by 14 weeks. Glenoid labrum, capsular ligament, coracohumeral ligament and superior glenohumeral ligament are seen by 10 weeks. Middle glenohumeral ligament is seen at 12-1/2 weeks while inferior glenohumeral ligament is seen at 14 weeks. Tendon of biceps is seen at 10 weeks. Conclusions: By 10 weeks of gestational age various structures of shoulder joint develop in situ, resembling in form and arrangement as those of adults. From these early stages, development proceeds rapidly to achieve adult characteristics. There are no intermediate stages in between where structures similar to those of lower forms i.e. syn/amphi artroses appear temporarily.